Reading by numbers : recalibrating the literary field - Bode, Katherine (Anthem scholarship in the digital age., 2012)
'Reading by Numbers: Recalibrating the Literary Field' explores the critical potential of digital and quantitative methods for producing new knowledge about literary and cultural history.